Digital literacy practices of English as a second language students: a case study at Mara University of Technology Malaysia - Kholidi, Muh. Azhar; Ariawan, Soni; Nurin Auni Syauqina Azhan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The rapid development of information and technologies demanded that students be wellversed in using digital tools, particularly in higher education contexts, to evaluate and use digital tools wisely. Therefore, within the qualitative approach, the present study attempted to gauge ESL students' digital literacy practices by exploring their concepts of digital literacy, the use of digital tools, and the purposes of using digital tools. Two postgraduate students studying ESL at Universiti Teknologi Mara, Malaysia, were purposively selected as the selected participants in the interview since they were available and eligible to be the respondents as postgraduate ESL students and experienced using digital literacy tools. The finding highlighted that students viewed digital literacy as the ability to communicate and understand the language of technology and the ability to utilise digital tools. They believed that digital literacy was beneficial to support their academic achievement and work for professional development. They frequently employed Microsoft Office, e-dictionary, and journal database searches to surmount their task. In addition, they tried to generate Internet-based marketing for working. Besides, the students personally develop digital tools for building relationships through personal communication via social media. In this case, they claimed that digital literacy enables them to appropriately filter, locate and disseminate information. Regarding digital tools, social media, and other platforms, such as YouTube, Facebook, Instagram, Twitter, etc., were heavily generated for academic and non-academic purposes. Knowing the suitable digital literacy tools for effective learning is pivotal for teachers to understand how their students learn.